Development of E-Module Based Learning Media for A1 Level Reading Competency - Putri Nanda; Herlina Jasa Putri Harahap (Indonesian Journal of Advanced Research, 2024)
The aim of this research is to develop E-module based learning media for A1 level reading literacy. This research was conducted in the library of the Faculty of Languages and Arts, Medan State University. In this research, creation research using Richey and Klein's theory is used. Among them are: (1) Planning stage, (2) Creation stage, (3) Evaluation stage. This research data consists of words, sentences and images on the topic "Hello!, Friends, Colleagues and Me and Off on holiday". The data source for this research comes from the book Studio Netzwerk A1 (Stefanie Dengler, Paul Rusch, Helen Schmitz and Tanja Sieber, 2012). The results of this research are learning media in the form of learning module applications uploaded to the Play Store. This application was created with the help of web-codular and validated by media experts and received an assessment of 85 (good) and a material expert assessment of 90 (very good).